2011
DOI: 10.4330/wjc.v3.i7.230
|View full text |Cite
|
Sign up to set email alerts
|

Implications of discoveries from genome-wide association studies in current cardiovascular practice

Abstract: Genome-wide association studies (GWAS) have identified several genetic variants associated with coronary heart disease (CHD), and variations in plasma lipoproteins and blood pressure (BP). Loci corresponding to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 64 publications
4
53
0
Order By: Relevance
“…Genome-wide association studies (GWAS) have identified LDLcholesterol-associated loci near HMGCR, ABO and TOMM40 [66], and also an association of TOMM40 with blood lipid levels [67,68] and body mass index [69]. Genetic variants in TOMM40/APOE-C1-C2-C4 genes have also been found to be associated with multiple cardiovascular-related traits [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified LDLcholesterol-associated loci near HMGCR, ABO and TOMM40 [66], and also an association of TOMM40 with blood lipid levels [67,68] and body mass index [69]. Genetic variants in TOMM40/APOE-C1-C2-C4 genes have also been found to be associated with multiple cardiovascular-related traits [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Genomewide association studies (GWAS) have iden tified LDLcholesterolassociated loci near HMGCR, ABO and TOMM40 [145], and also an association of TOMM40 with blood lipid levels [146,147] and body mass index [148]. Genetic variants in TOMM40/APOE-C1-C2-C4 genes have also been found to be associated with multiple cardiovascularrelated traits [149][150][151]. Several ABC transporters (ABCA1, ABCG1, ABCG5, ABCG8) have been shown to play important roles in the regulation of cellular cholesterol homeostasis by mediating cholesterol efflux.…”
Section: Cholesterol Dysregulationmentioning
confidence: 97%
“…Cyclin-dependent kinase inhibitor 2A (CDKN2A) and cyclin-dependent kinase inhibitor 2B (CDKN2B) genes both encode putative regulators of cyclin-dependent kinases on chromosome 9p21. Genome-wide association studies have identified that some CDKN2A or CDKN2B genetic variants are susceptible to CHD (8)(9)(10). As recently reported, many human diseases, including cardiovascular disease, could be influenced by aberrant DNA methylation modification (11).…”
Section: Introductionmentioning
confidence: 92%